2018
DOI: 10.1002/adfm.201706149
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Photocurrent Enhancements in Quantum Dot (QD)‐Sensitized MoS2 Devices on MoS2 Film Properties

Abstract: In this report we demonstrate highly efficient nonradiative energy transfer (NRET) from alloyed CdSeS/ZnS semiconductor nanocrystal quantum dots (QDs) to MoS2 films of varying layer thicknesses, including pristine monolayers, mixed monolayer/bilayer, polycrystalline bilayers and bulk-like thicknesses, with NRET efficiencies of over 90%. Large-area MoS2 films were grown on Si/SiO2 substrates by chemical vapor deposition (CVD). Despite the ultrahigh NRET efficiencies there is no distinct increase in the MoS2 pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…This behaviour is a consequence of the strong increase in dielectric screening with the addition of each MoS2 layer [4]. The incorporation of a sensitizing species on MoS2 photodetector devices has been shown to substantially increase the photocurrent and photoresponsivity of the devices [5]- [7]. In this contribution it is confirmed that the energy transfer mechanism in QD-sensitised MoS2 devices is Förster-type NRET.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…This behaviour is a consequence of the strong increase in dielectric screening with the addition of each MoS2 layer [4]. The incorporation of a sensitizing species on MoS2 photodetector devices has been shown to substantially increase the photocurrent and photoresponsivity of the devices [5]- [7]. In this contribution it is confirmed that the energy transfer mechanism in QD-sensitised MoS2 devices is Förster-type NRET.…”
Section: Introductionmentioning
confidence: 56%
“…One particular mechanism of energy transfer from the sensitizing species to the active material is Förster-type nonradiative energy transfer (NRET). This has been proven to be a highly efficient process in donor-acceptor pairs of quantum dots (QDs) and monolayer TMDs [3]- [5]. It has also been revealed that, in contrast to graphene, the NRET rate between QDs and MoS2 decreases as the layer number of the material increases.…”
Section: Introductionmentioning
confidence: 99%
“…An attractive method to overcome this thickness-limited absorption is to add a sensitizing material on top of the 2D material. There have been a few reports of dye sensitized [ 19 ] and quantum dot (QD) sensitized MoS 2 photodetectors [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. QDs in particular have the advantages of high quantum yield, broadband absorption, and tunable absorption wavelength by changing its size or composition.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the IGZO active layer has provided low modulated gate voltage, low subthreshold swing (SS), high on–off ratios and other electric properties for phototransistors . QDs and low‐dimensional materials can produce a high optoelectric conversion efficiency and rate, low dark current, high responsivity and detectivity for the phototransistor as a high‐performance integrated detector . However, key obstacles to their wide range of use in integrated‐photodetection applications must urgently be addressed.…”
mentioning
confidence: 99%
“…[5,6] QDs and low-dimensional materials can produce a high optoelectric conversion efficiency and rate, low dark current, high responsivity and detectivity for the phototransistor as a high-performance integrated detector. [7][8][9][10][11] However, key obstacles to their wide range of use in integrated-photodetection applications must urgently be addressed. For example, the wide-band semiconductor nature of IGZO leads to a low www.advopticalmat.de under an IR wavelength (1.5 µm) that is comparable to that of a commercial III-IV photodetector.…”
mentioning
confidence: 99%